Initiation, meaning and cessation of self-harm: Australian adults' retrospective reflections and advice to adolescents who currently self-harm. Issue 2 (3rd April 2022) - Hambleton, Ashlea L.; Hanstock, Tanya L.; Halpin, Sean; Dempsey, Caitlin
ABSTRACT: Self-harm remains a major health issue, particularly for adolescents. This qualitative study explored the reflections of adults who had self-harmed during adolescence. Foci included reasons for commencing and ceasing self-harm, as well as the perceived meaning of the self-harm and advice they would provide to adolescents currently engaging in self-harm. Participants included 185 adults aged 18 to 61 years, who had self-harmed at least once in adolescence. Participants responded to four qualitative questions that were part of a larger survey. Participants' responses were analyzed using either directed or conventional content analysis. Participants reported ambivalence about their self-harm with coexisting feelings of shame along with a recognition of the functions served by the behavior. The most frequently reported reasons for cessation included changes in personal relationships, frustration with shame, and receiving professional treatment. Most participants encouraged adolescents currently self-harming to seek help and to develop alternative coping mechanisms, although harm minimization also emerged as a theme. These findings are compared to international findings on reasons for initiation and cessation of self-harm as well as the advice for others. These insights may guide clinicians' understanding of motivations for adolescent self-harm and effective management of this behavior.